PREVENTION AND TREATMENT OF ERECTILE DYSFUNCTION IN PATIENTS AFTER RADICAL NERVESPARING PROSTATECTOMY - P. A. Karnaukh (Vestnik Urologii, 2015)
The purpose of our research is to improve the quality of life of patients undergoing radical prostatectomy. With the increasing frequency of prostate cancer and determining the effectiveness of surgical treatment significantly increased the number of radical prostatectomy. Surgical treatment is definitely in much greater extent when compared to radiation treatments related to the development of impotence, erectile dysfunction and urinary incontinence.The incidence of erectile dysfunction after prostatectomy ranges from 10 to 50%. Therefore, the development of new programmes for the rehabilitation of patients can improve their quality of life, due to the greater likelihood of recovery of erectile function after the operation. In our study we observed 84 patient. The incidence of erectile dysfunction was 76%. After applying one of the existing methods of stimulation: FDÈ5 inhibitors, intracavernose injections of prostaglandin, physical therapy, we were able to increase the effectiveness of treatment up to 54.8%, 40% and 70% respectively.